Evaluation of Gallic Acid-Coated Gold Nanoparticles as an Anti-Aging Ingredient - Yun-Zhen Wu; Yen-Yu Tsai; Long-Sen Chang; Ying-Jung Chen (MDPI AG, 2021)
Hyperglycemic environment-induced oxidative stress-mediated matrix metalloproteinase-1 (MMP-1) plays a crucial role in the degradation of the extracellular matrix (ECM), which might contribute to premature skin aging. Synthesized, environmentally friendly gallic acid-coated gold nanoparticles (GA-AuNPs) have been evaluated as an anti-aging antioxidant. Their microstructure was characterized by transmission electron microscopy (TEM), which showed that GA-AuNPs are spherical when prepared at pH 11. Dynamic light scattering (DLS) analysis revealed that the average hydrodynamic diameter of a GA-AuNP is approximately 40 nm and with a zeta potential of −49.63 ± 2.11 mV. Additionally, the present data showed that GA-AuNPs have a superior ability to inhibit high glucose-mediated MMP-1-elicited type I collagen degradation in dermal fibroblast cells. Collectively, our data indicated that high-glucose-mediated ROS production was reduced upon cell treatment with GA-AuNPs, which blocked p38 MAPK/ERK-mediated c-Jun, c-Fos, ATF-2 phosphorylation, and the phosphorylation of NFκB, leading to the down-regulation of MMP-1 mRNA and protein expression in high glucose-treated cells. Our findings suggest that GA-AuNPs have a superior ability to inhibit high-glucose-mediated MMP-1-elicited ECM degradation, which highlights its potential as an anti-aging ingredient.